Immune dysregulation and osteosarcoma: Staphylococcus aureus downregulates TGF‐β and heightens the inflammatory signature in human and canine macrophages suppressed by osteosarcoma. (15th October 2019) - Tuohy, Joanne L.; Somarelli, Jason A.; Borst, Luke B.; Eward, William C.; Lascelles, B. Duncan X.; Fogle, Jonathan E.
Abstract: Since William Coley utilized bacterial immunotherapy to treat sarcomas in the late 19th century, an association between infection and improved survival has been reported for human and canine osteosarcoma patients. One of the reasons for this improved survival is likely a reactivation of the host immune system towards an inflammatory anti‐tumour response, and one of the key players is the macrophage. Yet, despite their importance, the response of macrophages to infectious agents in the context of osteosarcoma has not been thoroughly evaluated. The aim of this study was to evaluate how in vitro exposure to a bacterial agent ( Staphylococcus aureus ) influenced canine and human macrophage differentiation in the presence of osteosarcoma. Our hypothesis was that S. aureus would, in the presence of osteosarcoma, induce a macrophage phenotype with significantly increased inflammatory signatures. Consistent with our hypothesis, human macrophages co‐cultured with osteosarcoma and S. aureus exhibited increased IFN‐γ, TNF‐α and IL‐12p70 cytokine secretion, decreased TGF‐β cytokine secretion and increased mRNA expression of TNF‐α when compared with macrophages co‐cultured with osteosarcoma and to macrophages cultured alone. Canine macrophages similarly exhibited increased IFN‐γ and TNF‐α cytokine secretion, decreased TGF‐β cytokine secretion, increased mRNA expression of TNF‐α and increased surface receptor expression of CD80 when co‐cultured with osteosarcoma and S. aureus . Collectively, the findings of this study suggest that infection upregulates the inflammatory immune response to counteract osteosarcoma‐induced immune suppression. This work informs a potential therapeutic strategy to optimize inflammatory stimuli for triggering an anti‐osteosarcoma macrophage response.